PENGARUH PROFITABILITAS, LEVERAGE, DAN KEPEMILIKAN PUBLIK TERHADAP PENGUNGKAPAN MANAJEMEN RISIKO - ASTUTI, APRI DWI; Istiqomah, Istiqomah; Apit, Wiwit (Medikonis, 2023)
This study aims to determine the impact of the Profitability and Leverage and Public Ownership on Risk Management Disclosure in Property and Real Estate Company from Indonesia Stock Market The type of research that will be used is research with quantitative research methods. By using the associative type. The population in this study were all permanent employees in Property and Real Estate Company from Indonesia Stock Market totaling 83 firm, the sampling technique used in this study is purposive sampling. and the total sample is 12 firm. Data analysis uses descriptive statistical analysis using SPSS Statistic software, the results of the work Profitability and Leverage don’t have any impact on Risk Management Disclosure, meanwhile Public Ownership have impact on Risk Management Disclosure